Comparative Legal Analysis of the Legislation of Labor Protection in Construction Using the Example of the EU, Azerbaijan and Ukraine - Bozhko, Volodymyr; Kulchii, Inna; SzydÅ‚o, Joanna (International Journal of Engineering and Technology, 2018)
The present article deals with the legislation on labor protection in the construction of the European Union and compares it with the law ofUkraineandAzerbaijan. The main focus of the paper is on Council Directive 92/57/EEC of 24 June 1992 on the implementation of minimum safety and health requirements at temporary or mobile construction sites. Comparing its content with the legislation on labor protection at the construction sites ofUkraineandAzerbaijan, the authors conclude that the guarantees of the right to labor protection in the EU cover a much wider range of subjects than in other states. This is due to the fact that the term Â«workerÂ», in accordance with the case-law of the Court of Justice, covers persons who performsÂ services for and under the direction of another person; pursues real, genuine activities, to the exclusion of activities on such a small scale as to be regarded as purely marginal and ancillary; in return for which he receives remuneration. In addition, guarantees of labor protection in the EU extend to the self-employed person, whose professional activity contributes to the completion of a project. Proposed ways to adapt Ukrainian and Azerbaijani legislation to EU law.Â Â